Investigation of energy efficient magnetorheological fluid (MRF) damper for application in prosthetic limb - Nor Hidayati Diyana binti Nordin (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
The use of dampers as shock absorbers in both transfemoral and transtibial prosthesis is important in order to provide comfort to the amputees without jeopardizing their health and safety. Three types of dampers are available namely active, semi-active and passive dampers. However, passive dampers are not suitable since the impedance data cannot be tuned and for active devices, they are not in favour due to its size and cost. In order to provide damping to the prosthesis that can be automatically tuned for normal walking conditions, magnetorheological fluid (MRF) damper can be used. MRF damper is a damper filled with magnetorheological fluid that reacts to the presence of magnetic field. It contains microsized particles, usually carbonyl iron particles which will align themselves forming chain-like structures parallel to the applied magnetic field. Thus, the rheology of the fluid is rapidly altered. The strength and distributions of the magnetic field influence the rigidity of the material, which directly affects the magnitude of force delivered by the damper. MRF damper needs an electromagnetic system to achieve “ON” state. Wearing a prosthetic limb that requires large power source accounts for inconveniency. Hence, to address this issue, there is a need for an energy efficient MRF damper that requires low power consumption so as to prolong its battery life. In this research, two areas were covered which are optimizing the energy efficient MRF damper as well as designing a suitable controller for an ankle prosthesis. In optimizing the dynamic range, this study will tackle the issue through MRF particles size and volume percentage ratio. COMSOL Multiphysics software was used in the optimization study and experiments were also conducted to verify the findings. It is shown that smallest particle size and highest particle ratio, which is 2μm at 0.6 particle ratio exhibits the highest wall shear stress, at a lesser amount of applied current. In addition, simulation works using fuzzy-PID (F-PID) controller was also developed to ensure the performance of the prosthetic limb equipped with MRF damper, which completed the research work from the perspective of mechatronics engineering. Using PID controller, the error goes up to 90% while a maximum of 20% percentage error is seen for a prosthetic limb with F-PID.